Experimental and Kinetic Modeling Studies on the Conversion of Sucrose to Levulinic Acid and 5-Hydroxymethylfurfural Using Sulfuric Acid in Water - Tan-Soetedjo, Jenny N M; van de Bovenkamp, Henk H; Abdilla, Ria M; Rasrendra, Carolus B; van Ginkel, Jacob; Heeres, Hero J (Industrial & engineering chemistry research, 2017)
We here report experimental and kinetic modeling studies on the conversion of sucrose to levulinic acid (LA) and 5-hydroxymethylfurfural (HMF) in water using sulfuric acid as the catalyst. Both compounds are versatile building blocks for the synthesis of various biobased (bulk) chemicals. A total of 24 experiments were performed in a temperature window of 80-180 °C, a sulfuric acid concentration between 0.005 and 0.5 M, and an initial sucrose concentration between 0.05 and 0.5 M. Glucose, fructose, and HMF were detected as the intermediate products. The maximum LA yield was 61 mol %, obtained at 160 °C, an initial sucrose concentration of 0.05 M, and an acid concentration of 0.2 M. The maximum HMF yield (22 mol %) was found for an acid concentration of 0.05 M, an initial sucrose concentration of 0.05 M, and a temperature of 140 °C. The experimental data were modeled using a number of possible reaction networks. The best model was obtained when using a first order approach in substrates (except for the reversion of glucose) and agreement between experiment and model was satisfactorily. The implication of the model regarding batch optimization is also discussed.